The value of furazolidone Nf-180 and Terramycin Bi-Con Tm 10 antibiotic in the rations of fattening pigs on alfalfa pasture. - Aubel, C.E. (Kansas Agricultural Experiment Station, 2011)
This experiment was initiated to study the effect of Furazolidone Nf-180 in rations for growing and fattening swine. In this test four lots of fall pigs were self-fed free choice a basal ration of shelled corn and a mixed protein supplement on alfalfa pasture. The mixed protein supplement was made up of 4 parts tankage, 4 parts soybean meal, 1 part linseed meal, and 1 part alfalfa meal. Lot 1 pigs received no nitrofuran. They were self-fed the basal ration, a mixed protein supplement, and shelled corn. Lot 2 pigs received shelled corn and a mixed protein supplement to which had been added Nf-180 at the rate of 2 ¼ pounds per ton. This supplied it to the pig at the rate of about 25 gms. per ton of total feed. Lot 3 pigs received the same feed ration as did those in lot 2 except that they also received Bi-Con TM-10 at the rate of 4 ½ pounds to a ton. Lot 4 pigs received shelled corn and a mixed protein supplement to which had been added Bi-Con 'fM-10 at the rate of 4 ½ pounds to a ton.
Keywords: Furazolidone; Terramycin; Alfalfa; Rations